2014
DOI: 10.3892/mmr.2014.2783
|View full text |Cite|
|
Sign up to set email alerts
|

Synergic effect between 5-fluorouracil and celecoxib on hypoxic gastric cancer cells

Abstract: 5‑fluorouracil (5‑FU) is commonly used in the treatment of gastric cancer; however, resistance to this drug occurs under hypoxic conditions. Celecoxib may be used to reverse this resistance. The aim of the present study was to elucidate the inhibitory effects and mechanisms of 5‑FU and celecoxib on the gastric cancer cell line SGC7901 under hypoxic conditions. SGC7901 cells were divided into four groups: Hypoxic control group, 5‑FU group, celecoxib group and 5‑FU/celecoxib combination group. Following treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 33 publications
1
2
0
Order By: Relevance
“…In keeping with previous reports [20, 52, 53], we observed that development of resistance to 5FU treatment is typically associated with the detection of ischemic areas within MCTS, whereas progress toward the development of necrotic areas within MTCS appears to associate with increasing resistance to treatment only at the highest dose tested. Accordingly, sensitivity to 5FU is associated to the presence of high percentages of Ki-67 proliferating cells in “early” stage MCTS.…”
Section: Discussionsupporting
confidence: 92%
“…In keeping with previous reports [20, 52, 53], we observed that development of resistance to 5FU treatment is typically associated with the detection of ischemic areas within MCTS, whereas progress toward the development of necrotic areas within MTCS appears to associate with increasing resistance to treatment only at the highest dose tested. Accordingly, sensitivity to 5FU is associated to the presence of high percentages of Ki-67 proliferating cells in “early” stage MCTS.…”
Section: Discussionsupporting
confidence: 92%
“…199 Furthermore, this combination showed a synergistic effect on gastric tumor growth inhibition by decreasing the mRNA and protein expression levels of hypoxia-inducible factor 2α, adenosine triphosphate-binding cassette subfamily G member 2, and octamer binding protein 4. 200,201 Additionally, the topical treatment with this combination was up to 70% more effective in reducing the number of UVB-induced skin tumors than 5-fluorouracil treatment alone. Thus, several phase I and II trials were designed and carried out on patients with hepatocellular carcinoma, 202 metastatic colorectal cancer, 203,204 or advanced esophageal 205 cancer.…”
Section: Clinical Studies Several Epidemiological and Clinicalmentioning
confidence: 98%
“…Several clinical and preclinical studies on the combinatory treatment of NSAIDs and chemotherapeutic agents have demonstrated synergistic antitumoral activity on different types of cancer, whether they are administrated alongside EGCG, , statins, curcumin, metformin, or DFMO. , Numerous studies have also demonstrated the enhancement in the antitumoral activity of different well-known chemotherapeutic drugs when administrated in combination with NSAIDs. These studies are outlined in Tables and , including cisplatin, sorafenib, doxorubicin, 5-fluorouracil, …”
Section: Summary and Perspectivesmentioning
confidence: 99%